2000
DOI: 10.2134/agronj2000.9251000x
|View full text |Cite
|
Sign up to set email alerts
|

Tillage, Cover Cropping, and Poultry Litter Effects on Cotton: II. Growth and Yield Parameters

Abstract: problems. Cotton seedlings are generally weak and conservation tillage can result in poor seedling establish-The development of conservation tillage systems for cotton (Gosment and poor crop growth due to soil compaction, sypium hirsutum L.), capable of reducing soil erosion and improving resulting in static or reduced cotton yields (Delaney, soil quality while increasing yields and profits, remains a challenge in the southeastern USA. Poor emergence and growth, delayed maturity,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 17 publications
(25 reference statements)
2
26
3
Order By: Relevance
“…Conservation tillage, such as NT or reduced till, can produce similar or higher cotton (Gossypium hirsutum L.) lint and sorghum (Sorghum bicolor L.) grain yields and biomass production than conventional till (Bordovsky et al, 1998;Nyakatawa et al, 2000;Torbert and Reeves, 1994). Similarly, legume cover crops can increase cotton lint and sorghum grain yields and biomass production compared with nonlegume or no cover crops because of increased N supply (Hargrove, 1986;Sainju et al, 2003;Touchton et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Conservation tillage, such as NT or reduced till, can produce similar or higher cotton (Gossypium hirsutum L.) lint and sorghum (Sorghum bicolor L.) grain yields and biomass production than conventional till (Bordovsky et al, 1998;Nyakatawa et al, 2000;Torbert and Reeves, 1994). Similarly, legume cover crops can increase cotton lint and sorghum grain yields and biomass production compared with nonlegume or no cover crops because of increased N supply (Hargrove, 1986;Sainju et al, 2003;Touchton et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Soil disturbance due to tillage usually modifies soil temperature with soils under CT tending to warm up faster than NT soils in spring (Nyakatawa and Reddy 2000). However, in this study, the high rainfall in spring, especially in 2009, most likely prevented the incidence of soil temperature differences between tillage systems.…”
Section: Soil Temperature and Moisture Contentmentioning
confidence: 69%
“…In addition, the higher CO 2 emissions in AN-SI plots can be attributed to increased biomass production in the form of crop residues from N application which directly adds C to the soil, which upon decomposition, can result in soil emission of CO 2 . Our studies comparing PL to AN sources of N on a Decatur silt loam soil have shown that inorganic N application generally results in better plant growth rate and higher biomass production compared to PL at the same application rate in the short term (Nyakatawa and Reddy 2000;Reddy et al 2009). Paustian et al (2000) also reported that N application to the soil can increase mineralization rates of soil organic matter by increasing residue input, which may also increase CO 2 emission.…”
Section: Soil Carbon Dioxide (Co 2 ) Fluxesmentioning
confidence: 84%
“…A conventional tillage approach for the cultivation of plants is most frequently used by farmers to reduce soil compaction, to improve aeration and to control weeds (Assis Ju´nior et al 2003;Franchini et al 2007;Crusciol et al 2008;Carvalho et al 2009). However, minimum tillage or no-till cropping are used to reduce erosion, to conserve moisture, to maintain and improve soil quality and to increase production (Doran et al 1998;Allmaras et al 2000;Nyakatawa et al 2000;Kladivko 2001). Current efforts focus on alternative systems to optimize the productivity and sustainability of agroecosystems, as well as to reduce production costs and environmental impacts on Brazilian soils (Franchini et al 2007).…”
Section: Introductionmentioning
confidence: 99%